The Relationship Between Locus of Control and Fear of Missing Out Among K-Pop Fans on Social Media - Adawiah, Zain (Program Studi Bimbingan dan Konseling, Fakultas Ilmu Pendidikan, Universitas Negeri Medan, 2023)
This study aims to examine the relationship between locus of control and fear of missing out (FoMO) among K-Pop fans (K-Popers) on social media. The research employed a quantitative correlational design with 200 participants, selected through a convenience sampling technique. Data were analyzed using the Spearman rank correlation test to identify the association between the two variables. The findings reveal that the dominant dimension of locus of control among participants was the external-chance factor, while the primary component influencing FoMO was anxiety. Furthermore, the analysis indicated a significant positive correlation between locus of control and FoMO, with a weak correlation strength of 19.6%. This suggests that the higher the external locus of control, the higher the level of FoMO experienced by K-Pop fans on social media. The results also indicate that individuals who are more externally oriented in their locus of control tend to depend on external validation and connection, which in turn fosters FoMO-related behaviors. This study contributes to the understanding of how personality factors influence digital behavior in fan communities, providing a psychological perspective on social media engagement among K-Pop fans.